Supporting Teachers to MASTER Science and Engineering Research Practices - Jackson, Jennifer; Hill, Kathleen M. (Innovations in Science Teacher Education, 2024)
Many secondary teachers often lack experience in actual science and engineering research, as their preparation programs are structured to lead to certification in a particular science field, with science learning constrained to participating in undergraduate lectures and lab courses. As a result, they often hold a view of research through the lens of the traditional scientific method in which research is linear, static, and sterile such that each step is discrete and only occurs when the prior step is complete (Windschitl, 2004; Windschitl et al., 2008). With a focus of NGSS on the science and engineering practices (SEPs), teachers need ongoing professional development that increases their understanding of the ways in which experts do their work and builds their capacity to incorporate these practices into student learning experiences. To address this need, the CSATS Research Experience for Teachers (RET) program introduces teachers to the Modeling Authentic STEM Research (MASTER)model, which serves as a useful tool and intervention for understanding high-level science and engineering research. Therefore, this paper presents an innovative framework that (1) allows teacher educators to create diagrammatic depictions of science and engineering research and (2) enables using these diagrams in programs with teachers. Through the creation of MASTER models, researchers can assist with bridging the communication gap that exists between scientists/ engineers and the K-12 community.